The house of the Fifers - Caudill, Rebecca 1899- (David McKay Co. Inc., 1954)
A fifteen-year-old girl does not look forward to spending the summer on her cousins' Kentucky farm, but, as she shares the family's problem of drought, she begins to learn many things about her own interests and capacities.